EVALUASI PEMBINAAN SUMBER DAYA APARATUR DI DINAS KELAUTAN DAN PERIKANAN PROVINSI KALIMANTAN TIMUR - Herwansyah . (Jurnal Paradigma (JP), 2017)
The purpose of this article is to explain the evaluation of apparatus development held by sea and fishery department of east Kalimantan province. The resukt states that the development of apparatus did not run optimal, but it can produce the competence apparatus. In the other side the increasing of apparatus competency precisely creates the gap between the work load with the apparatus competency it self.